Omicron wave during December 2022 - January 2023: access to pharmaceuticals and healthcare resources and impacts on health outcomes in Shenzhen, China - Jiayue Chen; Haisu Feng; Jiatong Sun; Yawen Jiang (Taylor & Francis Group, 2024)
ABSTRACTPurpose This study described pharmaceutical and medical resource accessibility of COVID-19 treatment in Shenzhen, China during the peak of COVID-19 infection from December 2022 to January 2023, and examined its influence on clinical outcomes.Methods We surveyed Shenzhen residents on COVID-19-related topics using electronic questionnaires. We conducted descriptive statistical analyses and multiple regressions including logistic and Tobit models to explore the impacts of resource constraints on patient outcomes. Resource utilisation and attempts to seek medical care were also described for severity-stratified subgroups.Results 76.8% of respondents reported experiencing COVID-19 symptoms between December 7, 2022 and January 29, 2023. Of those who attempted to purchase medication, 72.8% reported drug shortage. 49% of those seeking medical treatment experienced difficulties. Compared with those who did not experience drug shortages, those who did had an odds ratio of 1.959 (95% CI: 1.159 ∼3.313) of presenting with moderate to severe symptoms. Compared with those without difficulties in seeking medical treatment, those who did had an average of 0.39 (95% CI: 0.110 ∼0.670) more days absent from work.Conclusion Shenzhen residents with COVID-19 symptoms from December 2022 to January 2023 experienced a certain degree of pharmaceutical and medical resource constraints, which might have compromised their prognosis.